Konsep Pendidikan Islam di Era Digital dalam Kitab Tarbiyah Fi Zaman Al Fitan dan Pengaruhnya Terhadap Generasi Digital Native - Zain Fuad Hariri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The rapid development of digital technology has significantly influenced educational approaches, particularly in Islamic education for digital native generations. This study analyzes the concept of Islamic education in the digital era based on the book Tarbiyah fi Zaman al-Fitan by Sheikh Dr. Ali bin Yahya al-Haddadi and explores its influence on digital native generations. Using a qualitative approach with library research methodology, this study conducts an in-depth analysis of the primary source supplemented by relevant secondary literature including books, scientific journals, and previous research findings. The research integrates Digital Native theory, Social Cognitive theory, and Connectivism to understand the educational challenges faced by digital natives. The findings reveal four main pillars of Islamic education according to al-Haddadi: parental education, gradual education from early age (tarbiyah tadrijiyyah), creed education (aqidah), and social etiquette education (adab). These pillars effectively serve as protective measures against two main fitnah (trials) in the digital era: syahwat (lust) and syubhat (doctrinal confusion). The study demonstrates that classical Islamic educational concepts remain highly relevant for addressing contemporary digital challenges, providing internal firewall mechanisms, strengthening parental role modeling, and promoting adaptive collaborative learning. This research contributes to the development of Islamic educational frameworks that integrate classical spiritual values with modern digital literacy requirements.